The Unexpected Effects of L-Carnitine Supplementation on Lipid Metabolism in Hemodialysis Patients - Lea Katalinic; Branimir Krtalic; Bojan Jelakovic; Nikolina Basic-Jukic (Karger Publishers, 2018)
Background/Aims: There is a growing body of evidence that the long-term hemodialysis (HD) treatment leads to disturbances of carnitine homeostasis but the results of L-carnitine supplementation in HD patients have been conflicting. In the present prospective study, we investigated the effectiveness of intravenous L-carnitine in mitigating dialysis-related protein-energy wasting (PEW) based on pre-treatment albumin levels. Methods: Fifty patients (46% male, mean age 63±18.28 years, HD vintage 37.5 (7-288) months) received 1 g L-carnitine intravenously at the end of every HD session for 12 months. Clinical data were obtained from the medical records and charts. Intradialytic hypotension periods (defined as a decrease of systolic blood pressure by ≥ 20 mmHg) were recorded. Dietary habits were evaluated using a self-administered questionnaire prior to L-carnitine supplementation. Laboratory parameters were measured prior to the supplementation and controlled in 6-months intervals. Anthropometric measurements were performed prior to HD session, including "dry" body weight and height, body mass index (BMI), and body composition analysis using bioimpedance spectroscopy. Malnutrition-inflammation score (MIS) was used as a scoring system representing the severity of PEW and an indicator of general functional capacity. Results: A significant increase in total cholesterol, predominantly on the account of LDL was found (p=0.005). Simultaneously, HDL decreased (p=0.001) while triglyceride levels remained unchanged. Although the rise in serum prealbumin could be observed, lean tissue index (LTI) decreased and fat tissue index (FTI) increased which resulted in reduction of the LTI/FTI ratio (p=0.002). When divided into two groups according to the pre-treatment albumin values (< 35 g/L or ≥35 g/L), patients from the higher albumin group showed significant increase in prealbumin (p=0.005), and improved MIS (p=0.03). Multivariate regression analysis showed that higher FTI after introduction of L-carnitine led to greater hemodynamic stability (OR 1.709, 95% CI 1.006-2.905, p=0.048). As there was no differences in HD treatment characteristics, primery kidney disease or residual diuresis we could conclude that positive energy balance (with an increase in prealbumin and FTI) eventually led to better hemodynamic stability. Conclusion: Our results show significant effects of L-carnitine supplementation on lipid metabolism. Further clinical trials, as well as experimental research are needed to define the role of lipid metabolism in CKD population. Significant benefits of L-carnitine supplementation in patients with better initial serum albumin levels suggest that this therapy should not be restricted to patients with the worst nutritional and overall status.